Pembelajaran yang Menyenangkan pada Pelajaran Sejarah Kebudayaan Islam di MIS Al-Washliyah - Nasution, Abdul Gani Jamora; Utami, Anggi Putri; Adella, Sindy; Salbila, Isal; Aulia, Usna (Lembaga Yasin AlSys, 2023)
Enjoyable learning in SKI subjects needs to be widely understood. Fun learning is a learning process in which there is a strong relationship between the teacher and students, without any feelings of pressure. The purpose of this study was to find out about fun learning in the subject of Islamic Cultural History (SKI) at MIS Al-Washliyah. The method used in this research is a descriptive qualitative method. Based on the results of the research, it can be concluded that the implementation of learning carried out at MIS Al-Washliyah has been going well according to the Learning Implementation Plan (RPP). However, there are several obstacles that are felt in carrying out learning at MIS Al-Washliyah, namely the conditions and school environment, biological, physiological and psychological conditions of students ranging from interests, talents, intelligence to student motivation in learning. The solution that can be done in overcoming obstacles is by means of a learning environment that must be made conducive so that the learning process can be carried out optimally. To provide motivation to students, teachers must also be able to use interesting and fun learning methods such as experimental methods, discussions and others. As a teacher, you must also pay attention to student learning readiness.